The impact of the blight upon the pre-famine rural economy in ireland - Mcgregor, P (Economic & Social Studies, 1984)
Abstract: The efficiency wage model is developed in this paper to explain the radical restructuring of agricultural production towards cattle and sheep in Ireland that occurred after the blight attack of 1846. The pre-Famine structure and production changes consequent to the blight are examined statistically using cross sectional data at a county level. The paper concludes that the blight led to an increase in the wage floor which prevented the labour market clearing and which favoured livestock production by those producers who remained. Substantial emigration forced landlords to absorb a significant proportion of the loss due to the blight.
Keywords: Economics; Sociology